2015
DOI: 10.1002/hec.3212
|View full text |Cite
|
Sign up to set email alerts
|

Health Consequences of Rural‐to‐Urban Migration: Evidence from Panel Data in China

Abstract: This paper provides new empirical evidence on the health consequences of rural-to-urban migration in China. We use a panel dataset from 2003 to 2006 constructed by the Research Center on the Rural Economy at the Ministry of Agriculture in China to investigate the effects of short-term and medium-term migration on health status. By combining propensity-score matching and the difference-in-difference model, we attempt to overcome the migration endogeneity issue and estimate the average treatment effect on the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 48 publications
0
37
0
1
Order By: Relevance
“…Labor migration is common around the world, but many studies on it focus on its effect on regional development (Page and Plaza, ), while its microscopic effect on individuals is less clear (Stillman et al., ; Song and Sun, ). Research on effects of parental migration has mostly concentrated on its effect on children's academic performance (Lee, ; Antman, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Labor migration is common around the world, but many studies on it focus on its effect on regional development (Page and Plaza, ), while its microscopic effect on individuals is less clear (Stillman et al., ; Song and Sun, ). Research on effects of parental migration has mostly concentrated on its effect on children's academic performance (Lee, ; Antman, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main consensus is that the majority of rural migrants in cities lead second-class lives without much access to urban benefits. Studies have also suggested negative health and wellbeing consequences of rural-urban migration to migrants themselves (Song and Sun, 2015), and to the elderly and children left behind in the rural areas (Ao, Jiang, and Zhao, 2016;Li, Liu, and Zang, 2015;Xu and Xie, 2015;Murphy, Zhou, and Tao, 2015;Logan, 2011;De Brauw and Mu, 2011;Lee, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Although we have a comprehensive set of variables covering demographic, socio-economic and health characteristics, the possibility remains that if there are unobserved characteristics that would affect both individuals' changing public healthcare entitlements and healthcare utilisation, the standard PSM estimator would be biassed. To further improve identification, we utilise the difference-in-difference PSM method (Heckman et al, 1997;Song and Sun, 2016). This can be used to eliminate any time-invariant differences between the treatment and control groups, thereby allowing for selection on both observables and unobservables that are constant over time.…”
Section: Methodsmentioning
confidence: 99%